Femoral revision in periprosthetic fractures using a titanium modular fluted tapered stem: mortality and clinical and radiological outcomes. Issue 2 (December 2020) - Munegato, Daniele; Caminita, Agostino Dario; Sotiri, Romeo; Rossi, Andrea; Bigoni, Marco; Zatti, Giovanni
Introduction: The aim of the study was to evaluate the mortality and the outcomes of femoral revision in periprosthetic femoral fractures (PFF) using a titanium modular fluted tapered stem. Methods: We retrospectively reviewed femoral revisions performed for PFF with a titanium modular fluted tapered stem in 25 patients. The average age was 74.32 years. In 21 patients the type of fracture was Vancouver B2 and type B3 in 4 cases. The mean follow-up was 29.16 (0.83–104.1) months SD ± 29.49. Results: The 30-day and 1-year mortality were 8% and 12% respectively. The mean value of the Charlson Comorbidity Index was 4.8 and the mean value of ASA score was 2.4. The average time to surgery from admittance was 5.45 days with 20% of patients operated on within 48 hours. A significant correlation was found between ASA score and mortality. The mean HHS was 76 points; good-excellent results were recorded in 56% of patients. 72% had no pain and 28% had slight pain (VAS 1–3). 52% of patients were able to walk without pain, limp or aids. The mean implant subsidence was 1.57 mm and superior to 5 mm in 2 cases. As complications we recorded 4 implant dislocations (16%) and 2 infections. Reoperation rate was 12%. Conclusions: Femoral revision with a modular fluted tapered stem in patients with periprosthetic fractures results in good clinical and radiological outcomes. However, mortality remains high and, despite the modularity design, dislocation is the most frequent complication.